Factors Related to Work Stress in Nurses of COVID-19 Patients at Pandan Arang Boyolali Hospital - Wibawani, Eprami Mukti; Budiono , Irwan; Farida, Eko (Public Health Perspective Journal, 2025)
The results of a preliminary study conducted on nurses at Pandan Arang Hospital, Boyolali Regency, showed that 80% of nurses who handled COVID-19 patients had been confirmed positive for COVID-19. 75% of them experience work stress, preliminary survey results show that concerns about being infected with COVID 19 and increasing workloads are the main factors for work stress among nurses. This study aims to analyze what factors are related to work stress in nurses who provide services to COVID-19 patients at Pandan Arang Boyolali Regional Hospital. The study utilized a cross-sectional approach. The sample consisted of 76 nurses in the COVID-19 care unit determined through total sampling. Data collection was conducted using questionnaires, and data analysis was performed using bivariate analysis. The results of the multivariate analysis showed that job conflict (B = 1.636, p < 0.001) and family conflict (B = 0.634, p < 0.001) had a significant effect on work stress, while age, gender, and education level did not show a significant relationship with work stress (p > 0.05). The practical implication of this study is the importance of managing job conflict to reduce work stress.